Respuesta :
Solve the equation:-
[tex]5(4x - 4) = 5(3x + 3) \\ \cancel5(4x - 4) = \cancel5(3x + 3) \\ (4x - 4) = (3x + 3) \\ 4x - 3x = 4 + 3 \\ x = 7[/tex]
Verification:-
Put the value of X in equation:-
LHS:-
[tex]5(4x - 4) = 5(4(7) - 4) \\ 5(28 - 4) \\ 5(24) = 120[/tex]
RHS:-
[tex]5(3x + 3) = 5(3(7) + 3) \\ 5(21 + 3) \\ 5(24) = 120[/tex]
LHS= RHS
Hence proved
Answer:
x = 7
Step-by-step explanation:
Divide by 5 on each side :
- 5/5 (4x-4)=5/5 (3x+3)
- 4x - 4 = 3x + 3
Add 4 on each side :
- 4x - 4 + 4 = 3x + 3 + 4
- 4x = 3x + 7
Subtract 3x from each side :
- 4x - 3x = 3x + 7 - 3x
- x = 7